2016
DOI: 10.2298/mpns1602053r
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Kawasaki disease

Abstract: Kawasaki disease is the second most common vasculitis of childhood, so it should be included in the differential diagnosis for any child with a prolonged unexplained fever. Atypical Kawasaki disease should be taken into consideration in cases when not all clinical criteria are present but coronary abnormalities are documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Furthermore, atypical KD is characterized by a fever for a minimum of five days and the presence of two or three of the above criteria. The diagnosis of atypical KD is based on echocardiographic findings indicating the involvement of the coronary arteries [5,6,7] and the laboratory markers. McCrindle et al [7] suggested diagnostic pathways for suspected atypical patients with respect to the laboratory findings (white blood cell, WBC) count of ≥15,000 mm 3 , platelet count of ≥450,000 mm 3 , pyuria of ≥10 WBC/high-power field (HPF), albumin level of ≤3 g/dL, elevation of alanine aminotransferase (ALT) and anemia for age).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, atypical KD is characterized by a fever for a minimum of five days and the presence of two or three of the above criteria. The diagnosis of atypical KD is based on echocardiographic findings indicating the involvement of the coronary arteries [5,6,7] and the laboratory markers. McCrindle et al [7] suggested diagnostic pathways for suspected atypical patients with respect to the laboratory findings (white blood cell, WBC) count of ≥15,000 mm 3 , platelet count of ≥450,000 mm 3 , pyuria of ≥10 WBC/high-power field (HPF), albumin level of ≤3 g/dL, elevation of alanine aminotransferase (ALT) and anemia for age).…”
Section: Introductionmentioning
confidence: 99%
“…A doença de Kawasaki pode acarretar em diversas complicações para os pacientes, variando desde desordens cardiovasculares -como aneurisma de artéria coronária, infarto do miocárdio, aneurismas e ectasiasa complicações gastrointestinais, como obstrução intestinal, edema de cólon, isquemia intestinal; e neurológicas, dentre as quais podem ser citadas meningoencefalite, coleção subdural, hipoperfusão cerebral dentre outras (ALVES et al, 2011;RISTOVSKI et al, 2016;RODRIGUES et al, 2018). A complicação mais grave, no entanto, é a vasculite coronariana, a qual afeta de 15% a 20% dos pacientes não tratados.…”
Section: Discussionunclassified